2010
DOI: 10.1247/csf.10001
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of Twist2 and Erk in the Regulation of Osteoblastogenesis by HB-EGF-EGFR Signaling

Abstract: ABSTRACT. Epidermal growth factor (EGF) family members play important roles in the skeletal system. In this study, we examined the role of EGF receptor (EGFR) signaling in osteoblastogenesis in vitro. The expression of HB-EGF and epiregulin (EPR) was transiently induced within 24 h after osteogenic stimulation, but when preosteoblastic MC3T3-E1 cells were incubated with HB-EGF or EPR, osteoblast differentiation was inhibited. These effects were Ras-dependent, and ERK modulated Runx2 activity through the locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…Tenascin is synthesized by osteoblasts [35], and is able to stimulate osteoblastic differentiation through working with WNT signaling and BMP signaling [36]. Besides, parietal bone expressed higher levels of Msx2, Twist2, which are well-known transcriptional factor for osteoblast differentiation and bone formation [14, 37]. The higher levels of these genes expressions may account for osteoblast differentiation within parietal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Tenascin is synthesized by osteoblasts [35], and is able to stimulate osteoblastic differentiation through working with WNT signaling and BMP signaling [36]. Besides, parietal bone expressed higher levels of Msx2, Twist2, which are well-known transcriptional factor for osteoblast differentiation and bone formation [14, 37]. The higher levels of these genes expressions may account for osteoblast differentiation within parietal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Ferron et al (65) demonstrated that insulin signaling in osteoblasts increased osteoclast activity and thereby the level of uncarboxylated osteocalcin, thus affecting glucose homeostasis. Fulzele et al reported that insulin promotes osteoblast development and osteocalcin expression and that bone formation and the number of osteoblasts were reduced in mice without insulin receptors in bone (181,182). With age, these mice developed adiposity and insulin resistance (181).…”
Section: Metabolic Aspects In Relation To a Homeostatic Model Involvimentioning
confidence: 99%
“…The medium was changed every 3 days. For ALP and Alizarin red staining, the detailed procedures were described previously [17].…”
Section: In Vitro Osteoblastogenesis and Cell Stainingmentioning
confidence: 99%